Crisis, Neoliberalization and the Search for New Historic Bloc - Traykov, Bozhin (Identities: Journal for Politics, Gender and Culture, 2017)
Author(s): Bozhin Traykov Title (English): Crisis, Neoliberalization and the Search for New Historic Bloc Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 136-141 Page Count: 6 Citation (English): Bozhin Traykov, “Crisis, Neoliberalization and the Search for New Historic Bloc,” Identities: Journal for Politics, Gender and Culture, Vol. 14, No. 1 (Winter 2017): 136-141.